5.12.10 Problems 901 to 1000

Table 5.837: Third and higher order linear ODE

#

ODE

Mathematica

Maple

15295

\[ {}x^{3} y^{\prime \prime \prime }-4 y^{\prime \prime }+10 y^{\prime }-12 y = 0 \]

15307

\[ {}y^{\prime \prime \prime }+4 y^{\prime } = 0 \]

15308

\[ {}y^{\prime \prime \prime \prime }-y = 0 \]

15313

\[ {}y^{\prime \prime \prime }-9 y^{\prime } = 0 \]

15314

\[ {}y^{\prime \prime \prime \prime }-10 y^{\prime \prime }+9 y = 0 \]

15353

\[ {}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime } = 0 \]

15354

\[ {}y^{\prime \prime \prime \prime }+4 y^{\prime \prime } = 0 \]

15355

\[ {}y^{\prime \prime \prime \prime }-34 y^{\prime \prime }+225 y = 0 \]

15356

\[ {}y^{\prime \prime \prime \prime }-81 y = 0 \]

15357

\[ {}y^{\prime \prime \prime \prime }-18 y^{\prime \prime }+81 y = 0 \]

15358

\[ {}y^{\left (5\right )}+18 y^{\prime \prime \prime }+81 y^{\prime } = 0 \]

15359

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = 0 \]

15360

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y = 0 \]

15361

\[ {}y^{\prime \prime \prime }-8 y^{\prime \prime }+37 y^{\prime }-50 y = 0 \]

15362

\[ {}y^{\prime \prime \prime }-9 y^{\prime \prime }+31 y^{\prime }-39 y = 0 \]

15363

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime }+2 y^{\prime \prime }+4 y^{\prime }-8 y = 0 \]

15364

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+10 y^{\prime \prime }+18 y^{\prime }+9 y = 0 \]

15365

\[ {}y^{\prime \prime \prime }+4 y^{\prime } = 0 \]

15366

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+12 y^{\prime }-8 y = 0 \]

15367

\[ {}y^{\prime \prime \prime \prime }+26 y^{\prime \prime }+25 y = 0 \]

15368

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime }+9 y^{\prime \prime }+9 y^{\prime } = 0 \]

15369

\[ {}y^{\prime \prime \prime }-8 y = 0 \]

15370

\[ {}y^{\prime \prime \prime }+216 y = 0 \]

15371

\[ {}y^{\prime \prime \prime \prime }-3 y^{\prime \prime }-4 y = 0 \]

15372

\[ {}y^{\prime \prime \prime \prime }+13 y^{\prime \prime }+36 y = 0 \]

15373

\[ {}y^{\left (6\right )}-3 y^{\prime \prime \prime \prime }+3 y^{\prime \prime }-y = 0 \]

15374

\[ {}y^{\left (6\right )}-2 y^{\prime \prime \prime }+y = 0 \]

15375

\[ {}16 y^{\prime \prime \prime \prime }-y = 0 \]

15376

\[ {}4 y^{\prime \prime \prime \prime }+15 y^{\prime \prime }-4 y = 0 \]

15377

\[ {}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime }+16 y^{\prime }-16 y = 0 \]

15378

\[ {}y^{\left (6\right )}+16 y^{\prime \prime \prime }+64 y = 0 \]

15403

\[ {}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }-4 x y^{\prime }+4 y = 0 \]

15404

\[ {}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }+x y^{\prime }-y = 0 \]

15405

\[ {}x^{3} y^{\prime \prime \prime }-5 x^{2} y^{\prime \prime }+14 x y^{\prime }-18 y = 0 \]

15406

\[ {}x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }+7 x y^{\prime }-8 y = 0 \]

15407

\[ {}x^{4} y^{\prime \prime \prime \prime }+6 x^{3} y^{\prime \prime \prime }+15 x^{2} y^{\prime \prime }+9 x y^{\prime }+16 y = 0 \]

15408

\[ {}x^{4} y^{\prime \prime \prime \prime }+6 x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }-9 x y^{\prime }+9 y = 0 \]

15409

\[ {}x^{4} y^{\prime \prime \prime \prime }+2 x^{3} y^{\prime \prime \prime }+x^{2} y^{\prime \prime }-x y^{\prime }+y = 0 \]

15410

\[ {}x^{4} y^{\prime \prime \prime \prime }+6 x^{3} y^{\prime \prime \prime }+7 x^{2} y^{\prime \prime }+x y^{\prime }-y = 0 \]

15420

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime } = 1 \]

15487

\[ {}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime } = 12 \,{\mathrm e}^{-2 x} \]

15488

\[ {}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime } = 10 \sin \left (2 x \right ) \]

15489

\[ {}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime } = 32 \,{\mathrm e}^{4 x} \]

15490

\[ {}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime } = 32 x \]

15491

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = x^{2} \]

15492

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = 30 \cos \left (2 x \right ) \]

15493

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = 6 \,{\mathrm e}^{x} \]

15494

\[ {}y^{\left (5\right )}+18 y^{\prime \prime \prime }+81 y^{\prime } = x^{2} {\mathrm e}^{3 x} \]

15495

\[ {}y^{\left (5\right )}+18 y^{\prime \prime \prime }+81 y^{\prime } = x^{2} \sin \left (3 x \right ) \]

15496

\[ {}y^{\left (5\right )}+18 y^{\prime \prime \prime }+81 y^{\prime } = x^{2} {\mathrm e}^{3 x} \sin \left (3 x \right ) \]

15497

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = 30 x \cos \left (2 x \right ) \]

15498

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = 3 x \cos \left (x \right ) \]

15499

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = 3 x \,{\mathrm e}^{x} \cos \left (x \right ) \]

15500

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = 5 x^{5} {\mathrm e}^{2 x} \]

15529

\[ {}y^{\prime \prime \prime }-4 y^{\prime } = 30 \,{\mathrm e}^{3 x} \]

15530

\[ {}x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }+6 x y^{\prime }-6 y = x^{3} \]

15531

\[ {}x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }+6 x y^{\prime }-6 y = {\mathrm e}^{-x^{2}} \]

15532

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = \tan \left (x \right ) \]

15533

\[ {}y^{\prime \prime \prime \prime }-81 y = \sinh \left (x \right ) \]

15534

\[ {}x^{4} y^{\prime \prime \prime \prime }+6 x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }-9 x y^{\prime }+9 y = 12 \sin \left (x^{2}\right ) x \]

15542

\[ {}y^{\prime \prime \prime \prime }-8 y^{\prime \prime }+16 y = 0 \]

15547

\[ {}y^{\left (5\right )}-6 y^{\prime \prime \prime \prime }+13 y^{\prime \prime \prime } = 0 \]

15557

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+12 y^{\prime } = 8 \]

15560

\[ {}y^{\prime \prime \prime \prime }-16 y = 0 \]

15581

\[ {}y^{\prime \prime \prime }+8 y = {\mathrm e}^{-2 x} \]

15582

\[ {}y^{\left (6\right )}-64 y = {\mathrm e}^{-2 x} \]

15597

\[ {}y^{\prime \prime \prime }-27 y = {\mathrm e}^{-3 t} \]

15645

\[ {}y^{\prime \prime \prime }+9 y^{\prime } = \delta \left (t -1\right ) \]

15646

\[ {}y^{\prime \prime \prime \prime }-16 y = \delta \left (t \right ) \]

15783

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }+5 y^{\prime }+y = {\mathrm e}^{x} \]

15798

\[ {}y^{\prime \prime \prime }-4 y^{\prime \prime } = 0 \]

15799

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime } = 0 \]

15824

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime } = 0 \]

15825

\[ {}y^{\prime \prime \prime }-4 y^{\prime } = 0 \]

15839

\[ {}y^{\prime \prime \prime \prime }+\frac {25 y^{\prime \prime }}{2}-5 y^{\prime }+\frac {629 y}{16} = 0 \]

16367

\[ {}y^{\prime \prime \prime } = 0 \]

16368

\[ {}y^{\prime \prime \prime }-10 y^{\prime \prime }+25 y^{\prime } = 0 \]

16369

\[ {}8 y^{\prime \prime \prime }+y^{\prime \prime } = 0 \]

16370

\[ {}y^{\prime \prime \prime \prime }+16 y^{\prime \prime } = 0 \]

16371

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }-y^{\prime }+2 y = 0 \]

16372

\[ {}3 y^{\prime \prime \prime }-4 y^{\prime \prime }-5 y^{\prime }+2 y = 0 \]

16373

\[ {}6 y^{\prime \prime \prime }-5 y^{\prime \prime }-2 y^{\prime }+y = 0 \]

16374

\[ {}y^{\prime \prime \prime }-5 y^{\prime }+2 y = 0 \]

16375

\[ {}5 y^{\prime \prime \prime }-15 y^{\prime }+11 y = 0 \]

16376

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime } = 0 \]

16377

\[ {}y^{\prime \prime \prime \prime }-9 y^{\prime \prime } = 0 \]

16378

\[ {}y^{\prime \prime \prime \prime }-16 y = 0 \]

16379

\[ {}y^{\prime \prime \prime \prime }-6 y^{\prime \prime \prime }-y^{\prime \prime }+54 y^{\prime }-72 y = 0 \]

16380

\[ {}y^{\prime \prime \prime \prime }+7 y^{\prime \prime \prime }+6 y^{\prime \prime }-32 y^{\prime }-32 y = 0 \]

16381

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }-2 y^{\prime \prime }+8 y = 0 \]

16382

\[ {}y^{\left (5\right )}+4 y^{\prime \prime \prime \prime } = 0 \]

16383

\[ {}y^{\left (5\right )}+4 y^{\prime \prime \prime } = 0 \]

16384

\[ {}y^{\left (5\right )}+3 y^{\prime \prime \prime \prime }+3 y^{\prime \prime \prime }+y^{\prime \prime } = 0 \]

16385

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y = 0 \]

16386

\[ {}y^{\prime \prime \prime \prime }+8 y^{\prime \prime }+16 y = 0 \]

16387

\[ {}y^{\left (6\right )}+3 y^{\prime \prime \prime \prime }+3 y^{\prime \prime }+y = 0 \]

16388

\[ {}y^{\left (6\right )}+12 y^{\prime \prime \prime \prime }+48 y^{\prime \prime }+64 y = 0 \]

16389

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime } = 0 \]

16390

\[ {}y^{\prime \prime \prime }-y = 0 \]

16391

\[ {}y^{\prime \prime \prime \prime }+16 y^{\prime \prime \prime } = 0 \]